The best-selling pesticides in Brazil: Implications for the environment and health (Research, Society and Development, 2021)
The form and requirements for the commercialization of pesticides in Brazil, the release of new products and their adverse effects on health and ecosystems have been the subject of discussion by researchers and also by international controversies about food security in Brazil. These inputs are often persistent and difficult to be degraded, and may even generate more toxic metabolite intermediates. In this scenario, this work aimed to identify which pesticides were most sold in Brazil in the last 10 years, as well as to raise aspects associated with the biodegradation of these compounds and their effects on human health and the environment. For this, secondary data from the Brazilian Institute of the Environment and Renewable Resources (IBAMA) were used, in addition to a bibliographic review and quali-quantitative method. The results show that the agrochemicals that led the ranking of the most commercialized were glyphosate; 2,4D and atrazine. There was a large gap in knowledge about the biodegradation processes of these products, although there are studies that show the relevance of the subject for mitigating impacts on human health and ecosystems. The consulted literature also revealed a wide range of adverse effects on human health resulting from exposure to these agrochemicals. Finally, it was considered urgent to change the pattern of consumption of these active ingredients (i.a.) and the search for less impacting alternatives aimed at sustainable development.